Experimental and Numerical Studies on Setback Buildings Considering the SSI Effect under Seismic Response - R. M. Thejaswini; L. Govindaraju; V. Devaraj (Civil Engineering Journal, 2021)
From the previous studies it is observed that due to the effect of the earthquake, several irregular buildings failed vulnerably. Further the effect of sub soil conditions where these buildings have been founded also play an important role on the seismic response of these buildings. In the past, experimental studies on the seismic response of different setback building configurations have not been carried out. Therefore, in the present study the seismic behaviour of setback buildings considering Soil Structure Interaction (SSI) has been evaluated by conducting experimental and numerical investigations. Buildings with various setback configurations were considered and are designed as pile foundation supported structures. The irregularity index of these building configurations have been determined as per the existing codal provisions. These piles supported buildings representing the prototype structure have been scaled down according to geometric, kinematic and dynamic scaling laws. The scaled building models are subjected to vibrations beyond resonant frequencies using shake table facility. A comparison of the results has been made between experimental and numerical investigations. Based on the study it has been observed that storey displacements of building with regular configurations are higher in comparison with the setback buildings. It is also found that asymmetrical and symmetrical setback buildings having different irregularity indices as per IS:1893-2016 indicate nearly the same displacements at resonant frequencies. Doi: 10.28991/cej-2021-03091664 Full Text: PDF